« L’âme faite à partir des ītyē » : l’essai de reconstruction de la psychologie de Bardesane - Jurasz, Izabela (Zeitschrift für antikes Christentum, 2024)
The study of Bardesane’s anthropological teachings comes up against testimonies that are difficult to interpret and reconcile. Information about the "soul made of elements" and allusions to atomistic theory cannot be fitted into a tripartite anthropological scheme that observes the separation of soul and body. This article examines Bardesanite anthropology in relation to cosmology and physics. By highlighting Bardesanism’s peculiarities, namely the theory of qualities-atoms (perde) component of elemental masses (itye), we can reconstruct its teaching on human origin, constitution and destiny.